Pengembangan Laboratorium Multimedia Virtual sebagai Media Pembelajaran Audio Digital menggunakan Model Game First Person Shooter - Iwan Sonjaya; Noorlela Marcheta; Prayoga Bayu Lail Segara (Sekawan Institut, 2024)
The laboratories at PNJ cannot be operated optimally because the available equipment does not yet have equipment with the latest technology. Whereas students should be able to practice theories related to the latest technology so that equipment is needed that continues to change in line with current technological developments. However, the situation in changing the existing technology requires a bureaucracy that is quite complicated and long. Virtual laboratories are media used to help understand a subject matter and can be a solution to the limitations or absence of laboratory equipment that can be upgraded more easily. Acceleration in the world of education is also re-sponded to by shifting the function of the laboratory. In addition, this virtual laboratory can also be utilized as a distance learning tool. This application is made using the MDLC (Multimedia De-velopment Life Cycle) method which has 6 stages, namely, concept, design, material collecting, assembly, testing, and distribution. The virtual laboratory in audio multimedia learning has been successfully created using the First Person View model. This success is based on the results of testing from 37 responders through 11 questions posed to users who have tried the application found that the respondent's interpretation of the ease of use of the application in learning is 85.40%. While 81.62% stated that the Digital Audio Laboratory already had a feel like a real lab and 85.94% stated that participants were interested in learning through a virtual digital audio laboratory.